Effect Of Training and Development Programs on Perceived Employees Job Performance in Selected Insurance Companies in Lagos State - Olanipekun, Lateef Okikiola; Olanipekun, Deborah Oluwayimika (Periodica Journal, 2022)
Several studies on employees training and development were mostly conducted in public corporations and their private counterparts such as banks, communication industries and manufacturing industries with little exploration of research in the insurance sector. Hence, this study examined the effect of training and development on perceived employees job performance in selected insurance companies in Lagos State with the objective of identifying the common training and development programmes; investigating the frequency of training and development programmes; and assessing the perceived effect of these training and development programmes on employees job performance in selected insurance companies in Lagos State. The study was anchored on Douglas McGregor’s Theory X and Theory Y. A sample size of 137 employees from three selected insurance companies namely Mutual Benefits Assurance plc, Oasis Insurance and Mansard Insurance were selected using simple random sampling technique; data obtained were analysed through SPSS and presented using simple percentages and frequency distribution. Findings from the study revealed that the common training and development programmes in the selected Insurance companies were on customer relationship management, financial security; cyber security, training on falsification and fraud, etc; and these training and development programmes are held on a weekly basis. The study concluded that training and development programmes in the selected insurance companies have greatly influenced organisational growth by increasing the customer base and facilitating smooth functioning of the organisation with little or no supervision of the management. Therefore, there should be increased periodic assessment, appraisal and evaluation of every training organised for the employees and training should consider the personal challenges faced by employees in their peculiar departments rather than being given general trainings.
Keywords: Employees; Evaluation and Appraisal; Insurance Companies; Periodic assessment